Antibacterial Activity and Cytotoxicity of Three Lectins Purified from Drumstick (Moringa oleifera Lam.) Leaves - Khatun, Shahanaz; Khan, MMH; Ashraduzzaman, M; Pervin, Farzana; Bari, Luthfunnessa; Absar, N (Journal of Bio-Science, 2011)
Context: Plant materials contain glycoproteins (phytolectins) that are toxic in nature may play a key role in the control of various normal and pathological processes in living organisms and have diverse biochemical and diagnostic applications. Objectives: Screening of three lectins SLL-1, SLL-2 and SLL-3 purified from Drumstick (Moringa oleifera Lam.) leaves for their antibacterial activities and brine shrimp lethality bioassay. Materials and Methods: Three bioactive lectins were purified from Drumstick leaves by conventional chromatographic methods. The lectins were tested for their antibacterial activities against three pathogenic bacteria- Escherichia coli (gram-negative) Shigella dysenteriae (gram-negative) and Staphylococcus aureus (gram-positive) using the standard disc-diffusion method. Mortality of the brine shrimp naupli was assessed by hality bioassay. Results: All the lectins showed antibacterial activity against E. coli, Sh. dysenteriae and St. aureus. They also showed cytotoxic effect in brine shrimp (Artemia salina L.) lethality bioassay. The LC50 values of SLL-1, SLL-2 and SLL-3 were found to be 15.8, 17.78 and 14.12 μg/ml respectively. The experimental results revealed that SLL-3 is more cytotoxic than other lectins. The lectin SLL-3 showed lowest activity whereas SLL-1 showed highest activity against the three bacteria. Conclusion: Results suggest that the extracts from M. oleifera leaf can be a source of natural antimicrobials with potential applications in pharmaceutical industry to control coliform bacteria. Key words: Drumstick; Moringa oleifera; lectins; antibacterial activity; brine shrimp; bioassay DOI: 10.3329/jbs.v17i0.7112 J. bio-sci. 17: 89-94, 2009